Consumer Satisfaction as a Mediation on Repurchasing Interest on Price, Promotion, and Quality of Service - Suwarno, Aldo; Estining Rahayu, Caecilia Wahyu; Fridayani, Januari Ayu (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2022)
The purpose of this research is to determine the following: (1) the effect of price on repurchase interest as mediated by consumer satisfaction, (2) the effect of promotion on repurchase interest as mediated by consumer satisfaction, and (3) the effect of service quality on repurchase interest as mediated by consumer satisfaction. Purposive sampling was employed as a sample strategy. Data was collected by sending out online surveys to 100 people. Partial Least Squares and WarpPLS 6.0 are used in the data analysis technique. According to the findings of this study, (1) consumer satisfaction moderates the effect of price on consumer repurchase interest, (2) consumer satisfaction has little effect on consumer repurchase intention when it comes to promotions, (3) consumer satisfaction does not affect repurchase intention when it comes to service quality.